2022
DOI: 10.1371/journal.pgph.0000318
|View full text |Cite
|
Sign up to set email alerts
|

Discharge instructions given to women following delivery by cesarean section in Sub-Saharan Africa: A scoping review

Abstract: Objective A scoping review of discharge instructions for women undergoing cesarean section (c-section) in sub-Saharan Africa (SSA). Method Studies were identified from PubMed, Globus Index Medicus, NiPAD, EMBASE, and EBSCO databases. Eligible papers included research based in a SSA country, published in English or French, and containing information on discharge instructions addressing general postnatal care, wound care, planning of future births, or postpartum depression targeted for women delivering by c-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Across several studies, women delivering via cesarean in Rwanda reported a lack of instructions or conflicting instructions at the time of discharge 8–10 . A scoping review found that very few studies based in SSA comment on cesarean recovery activities or postoperative care pathways after hospital discharge, and even fewer studies provide concrete recommendations 11 . Here, we outline recommendations for discharge instructions to be provided to women who have given birth by cesarean in SSA to optimize their recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across several studies, women delivering via cesarean in Rwanda reported a lack of instructions or conflicting instructions at the time of discharge 8–10 . A scoping review found that very few studies based in SSA comment on cesarean recovery activities or postoperative care pathways after hospital discharge, and even fewer studies provide concrete recommendations 11 . Here, we outline recommendations for discharge instructions to be provided to women who have given birth by cesarean in SSA to optimize their recovery.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 A scoping review found that very few studies based in SSA comment on cesarean recovery activities or postoperative care pathways after hospital discharge, and even fewer studies provide concrete recommendations. 11 Here, we outline recommendations for discharge instructions to be provided to women who have given birth by cesarean in SSA to optimize their recovery. These recommendations were developed through expert consensus with a focus on rural Rwanda and discussions on how these instructions could be generalized to other SSA contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In five countries (the Dominican Republic, Brazil, Cyprus, Egypt, and Turkey), caesarean sections surpass vaginal deliveries [9,12]. Conversely, in the least Women 2024, 4 developed countries, merely about 8% of women undergo caesarean section, with a meager 5% in sub-Saharan Africa, illustrating a disconcerting lack of access to this lifesaving procedure [9,13]. The World Health Organization recommended a CS range of 10-15% for countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies report a complete lack of or less information regarding home care after CS compared to home care after vaginaly delivery [ 23 , 24 ]. The limited available information about home care after CS highly varies among different sources across the region [ 25 ]. Post-discharge instruction, especially for post-CS mothers has been a neglected aspect of post-CS care for a long time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%